Dual-tracer positron emission tomography/computed tomography as an imaging probe of de novo lipogenesis in preclinical models of hepatocellular carcinoma - Tsao, Chin-Ho; Jhou, Rong-Hong; Ke, Chien-Chih; Chang, Chun-Wei; Chang, Chi-Wei; Yang, Bang-Hung; Huang, Wen-Sheng; Shih, Bing-Fu; Liu, Ren-Shyan (Frontiers in Medicine, 2022)
Background De novo lipogenesis is upregulated in many cancers, and targeting it represents a metabolic approach to cancer treatment. However, the treatment response is unpredictable because lipogenic activity varies greatly among individual tumors, thereby necessitating the assessment of lipogenic activity before treatment. Here, we proposed an imaging probe, positron emission tomography/computed tomography (PET/CT) with dual tracers combining 11C-acetate and 18F-fluorodeoxyglucose (18F-FDG), to assess the lipogenic activity of hepatocellular carcinoma (HCC) and predict the response to lipogenesis-targeted therapy. Methods We investigated the association between 11C-acetate/18F-FDG uptake and de novo lipogenesis in three HCC cell lines (from well-differentiated to poorly differentiated: HepG2, Hep3B, and SkHep1) by examining the expression of lipogenic enzymes: acetyl-CoA synthetase 2 (ACSS2), fatty acid synthase (FASN), and ATP citrate lyase (ACLY). The glycolysis level was determined through glycolytic enzymes: pyruvate dehydrogenase expression (PDH). On the basis of the findings of dual-tracer PET/CT, we evaluated the treatment response to a lipase inhibitor (orlistat) in cell culture experiments and xenograft mice. Results Dual-tracer PET/CT revealed the lipogenic activity of various HCC cells, which was positively associated with 11C-acetate uptake and negatively associated with 18F-FDG uptake. This finding represents the negative association between 11C-acetate and 18F-FDG uptake. Because these two tracers revealed the lipogenic and glycolytic activity, respectively, which implies an antagonism between lipogenic metabolism and glucose metabolism in HCC. In addition, dual-tracer PET/CT not only revealed the lipogenic activity but also predicted the treatment response to lipogenesis-targeted therapy. For example, HepG2 xenografts with high 11C-acetate but low 18F-FDG uptake exhibited high lipogenic activity and responded well to orlistat treatment, whereas SkHep1 xenografts with low 11C-acetate but high 18F-FDG uptake exhibited lower lipogenic activity and poor response to orlistat. Conclusion The proposed noninvasive dual-tracer PET/CT imaging can reveal the lipogenesis and glycolysis status of HCC, thus providing an ideal imaging probe for predicting the therapeutic response of HCC to lipogenesis-targeted therapy.